Natural Democracy of Minangkabau in the Era of West Sumatra Provincial Regulation Number 7 of 2018 concerning Nagari: Towards Consolidation? - Gunawan, Andre; Putera, Roni Ekha; Zetra, Aidinil (STIA Adabiah, 2024)
Democracy at the local tier exhibits intricate dynamics and possesses substantial variances, one of which pertains to the democratic framework in Nagari, West Sumatra. The West Sumatra Provincial Regulation 7/2018 delineates an interpretation of Nagari through the principle of territorial unity within the governmental structure of Nagari. In alignment with its legal authority, West Sumatra Provincial Regulation 7/2018 encompasses a conceptualization of Nagari infused with the essence of Traditional Village, achieved through establishing Nagari institutions aimed at fortifying customary practices. This fortification is directed towards the component of traditional leaders, which signifies a hallmark of the Minangkabau cultural entity. Traditional leaders, or tribal chiefs, have diminished their authoritative power due to the polarization of political institutions governing the village. The West Sumatra Provincial Regulation 7/2018 advocates for governmental institutions to reinforce traditional stakeholders or leaders alongside their inherent rights. In this regard, West Sumatra Provincial Regulation 7/2018 elevates the status of traditional leaders, who have traditionally occupied roles within community institutions, to positions of prominence within governmental frameworks. This elevation is predicated on the premise that conventional leaders embody the essence of tradition itself, serving as figures who exemplify leadership and uphold the distinctive characteristics of the village populace as dictated by traditional norms.